Про явище алотези - Бурковський, І.3. (Мовознавство, 2007)
Статтю присвячено одному з важливих аспектів глибинних етимологічних зв’язків —
вільному чергуванню кореневих приголосних у різних прамовах, віддалено споріднених між
собою, насамперед семітській та індоєвропейській. Стисло висвітлюється історія вивчення
проблеми, докладніше обговорюється досить ґрунтовне дослідження Соломона Майзеля. The article is dedicated to an important aspect of the profound etymological connections — to
the free alternation of the root consonants in some distantly related parent languages, mainly in the
Proto-Semitic and the Proto-Indo-European. A brief survey of the hitherto performed investigations
is given, with a more detailed attention on a prominent work of Solomon Maizel.